PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH (SAKD), PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Indrawan Maulana; M. Cholid Mawardi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study is to provide evidence about the influence of human resource competence, application of regional financial accounting system, use of information technology, and internal control system on quality of local government financial reports. This study uses primary data by providing a questionnaire. The population in this study were financial employees of the Malang Raya Regional Government. The sampling technique used purposive sampling method with predetermined criteria for respondents. Hypothesis testing in this study used simultaneous test (F test), coefficient of determination (R square), and partial test (t test). From the results of this study interpreted that simultaneously the variables of human resource competence, application of regional financial accounting system, use of information technology, and internal control system have an effect on quality of local government financial reports. Partially the human resource competency variables and internal control system have an effect on quality of local government financial reports. Whereas partially the variables of application of regional financial accounting system and use of information technology have no effect on quality of local government financial reports. Keywords : Human Resource Competence, Application of the Regional Financial Accounting System, Use of Information Technology, Internal Control System, and Quality of Local Government Financial Reports.